2022
DOI: 10.3390/healthcare10071334
|View full text |Cite
|
Sign up to set email alerts
|

School Students’ Concerns and Support after One Year of COVID-19 in Austria: A Qualitative Study Using Content Analysis

Abstract: Adolescents suffer severely from the psychological consequences of the COVID-19 pandemic. Using qualitative content analysis, this study examined open-ended responses to a survey on the mental health of school students in Austria in February 2021. A representative sample (n = 214) was drawn from a total survey sample of 3052 adolescents aged 14–20. The analysis revealed several areas of concern, including school-related concerns, concerns about restrictions, self-related concerns, and interpersonal problems. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 52 publications
0
23
0
4
Order By: Relevance
“…For those who are still in education or transitioning to working life, the pandemic has led to an interruption of education and employment biographies ( 51 ). As the pandemic progresses and economic problems increase, studies reveal growing fears among young people regarding learning outcomes and prospects ( 52 , 53 ). Unemployment rates for young people under 25 in Austria were almost twice as high as in the general population in February 2022 ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…For those who are still in education or transitioning to working life, the pandemic has led to an interruption of education and employment biographies ( 51 ). As the pandemic progresses and economic problems increase, studies reveal growing fears among young people regarding learning outcomes and prospects ( 52 , 53 ). Unemployment rates for young people under 25 in Austria were almost twice as high as in the general population in February 2022 ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the significance of social life for apprentices. Qualitative research on the resources of similar-aged school students also showed that social contacts were reported as their main resource to deal with pandemic-related stressors [ 47 ]. In addition, peer relationships protect against psychological problems or help to cope with them better [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was of further concern that despite the poor evidence on apprentices’ mental health [ 33 ], only a small proportion (2.64%) mentioned professional help, e.g., seeing a psychotherapist or psychologist, as a resource. Thus, even fewer apprentices seemed to seek professional help than the already low percentage (3.3%) of school students [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…While positive effects on family cohesion, personal growth, and sleep duration were discussed, these were mostly diminished by reduced coping opportunities, leading to a decline in well-being and mental health, increased feelings of loneliness, increased potential for family conflicts, and decreased school performance [ 8 , 9 , 10 , 11 , 12 , 13 ]. A qualitative study of Austrian students using content analysis reported school-related concerns and concerns about restrictions as the most burdensome, while social and recreational activities were mentioned as the strongest protective sources [ 14 ].…”
Section: Introductionmentioning
confidence: 99%